Dr. Feyi Ademola-Adeoye and Dr. Eric Anchimbe on Nigerian Proverbs - Ademola-Adeoye, Feyisayo; Anchimbe, Eric (Cluster Conversations, 2025)
In this latest episode of Cluster Conversations, Associate Professor Dr. Eric Anchimbe sits down with Dr. Feyi Ademola-Adeoye, Senior Research Fellow at the University of Lagos and a 2025 fellow at the Bayreuth Academy. Together, they delve into the evolving world of Nigerian proverbs and explore how younger generations are remixing and reinterpreting these age-old sayings to reflect today’s social realities. From the streets to social media, from tradition to satire, this conversation examines how language evolves with culture. Ademola-Adeoye unpacks the creative ways Gen Z is turning conventional wisdom on its head – sometimes humorously, sometimes critically – to challenge inherited norms and speak to current struggles. But why are today’s youth giving grandma’s proverbs a modern twist? What does it say about shifting values, hardship, and identity in contemporary Nigeria? And can a proverb still guide us if it’s been reimagined on Instagram? Tune in for a lively and insightful exchange, including a few post-proverbials you won’t forget.